LOCAL GOVERNMENT INNOVATIONS IN THE COVID-19 PANDEMIC: Public Perceptions of the Implementation of the Behambinan Local e-Commerce Application in Samarinda City - Letizia Dyastari; Budiman Budiman; Tengku Imam Syarifuddin (DIA: Jurnal Administrasi Publik, 2021)
In this study, the authors looked at local government innovations that focused on the Samarinda City Government in the midst of the Covid-19 pandemic. The focus of this research is on people's perceptions of local e-commerce applications which are the innovations of the Samarinda City Government in Handling Covid-19. This research is qualitative research using a qualitative descriptive approach. The data used in this study are premiere data obtained through online surveys and the play.google.com website as support. In addition, the author also made observations on the Behambinan application to obtain more in-depth data. The results showed that only 24 percent of respondents knew about the Behambinan e-commerce application. This is because the socialization carried out by the Samarinda City Government is not optimal. The lack of socialization affects people to prefer e-commerce that is familiar in society. In addition, the local e-commerce application Behambinan is not only used as innovation during a pandemic, but its realization must touch and have an impact on society.